2020
DOI: 10.1177/1934578x20910548
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Curcumin on Acrylamide-Induced Hepatic and Renal Impairment in Rats: Involvement of CYP2E1

Abstract: As a chemical extensively used in industrial areas and formed during heating of carbohydrate-rich foods and tobacco, acrylamide (ACR) has been demonstrated to exert a variety of systemic toxic effects including hepatotoxicity and nephrotoxicity. In the present study, we investigated the effect of curcumin, a natural polyphenolic compound in a popular spice known as turmeric, on the hepatic and renal impairment caused by ACR exposure to 40 mg/kg for 4 weeks in rats. The administration of curcumin at doses of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
0
21
0
2
Order By: Relevance
“…In recent years, evidence on its hepatotoxicity has been reported, for the liver is the main site of AA biotransformation. Sun et al reported that when rats were intraperitoneally injected with 40 mg/kg AA for four weeks, the levels of serum ALT and AST were markedly higher in the treated group than in the normal control group [ 38 ]. Additionally, AA (20 mg/kg) increased the levels of liver oxidative stress markers, including protein carbonyl content, nitric oxide, and lipid peroxides, but markedly decreased the activity of liver antioxidants, including superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, evidence on its hepatotoxicity has been reported, for the liver is the main site of AA biotransformation. Sun et al reported that when rats were intraperitoneally injected with 40 mg/kg AA for four weeks, the levels of serum ALT and AST were markedly higher in the treated group than in the normal control group [ 38 ]. Additionally, AA (20 mg/kg) increased the levels of liver oxidative stress markers, including protein carbonyl content, nitric oxide, and lipid peroxides, but markedly decreased the activity of liver antioxidants, including superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatotoxic group (Group II): Rats received oral administration of acrylamide at a dose of 50 mg/kg body weight for four weeks [7] .…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Acrylamide [50 mg/kg/day] was dissolved in 10 ml distilled water, so each 1 ml distilled water contained 5 ml acrylamide. Each rat was given distilled water containing acrylamide by weight and orally administered to rats for four weeks via gastric intubation [7] .…”
Section: Hepatotoxic Plus Ginger Group (Group Iv)mentioning
confidence: 99%
“…Moreover, acrylamide is now classified by the International Agency for Research on Cancer as a probable human carcinogen 3 . As a small unsaturated amide, AC is absorbed readily by humans and animals after ingestion and distributed into several vital organs such as the thymus, heart, brain, liver, and kidney, where it may induce toxicity or carcinogenicity 4 .…”
Section: Introductionmentioning
confidence: 99%